The Virtual International Stroke Trials Archive - Ali, Myzoon; Bath, Philip M. W.; Curram, John; Davis, Stephen M.; Diener, Hans-Christoph; Donnan, Geoffrey A.; Fisher, Marc; Gregson, Barbara A.; Grotta, James; Hacke, Werner; Hennerici, Michael G.; Hommel, Marc; et al. (Stroke, 2007)
BACKGROUND AND PURPOSE: Stroke has global importance and it causes an increasing amount of human suffering and economic burden, but its management is far from optimal. The unsuccessful outcome of several research programs highlights the need for reliable data on which to plan future clinical trials. The Virtual International Stroke Trials Archive aims to aid the planning of clinical trials by collating and providing access to a rich resource of patient data to perform exploratory analyses. - METHODS: Data were contributed by the principal investigators of numerous trials from the past 16 years. These data have been centrally collated and are available for anonymized analysis and hypothesis testing. - RESULTS: Currently, the Virtual International Stroke Trials Archive contains 21 trials. There are data on >15,000 patients with both ischemic and hemorrhagic stroke. Ages range between 18 and 103 years, with a mean age of 69+/-12 years. Outcome measures include the Barthel Index, Scandinavian Stroke Scale, National Institutes of Health Stroke Scale, Orgogozo Scale, and modified Rankin Scale. Medical history and onset-to-treatment time are readily available, and computed tomography lesion data are available for selected trials. - CONCLUSIONS: This resource has the potential to influence clinical trial design and implementation through data analyses that inform planning.
Gesehen am 09.12.2014